Nilai Heuristik dalam Sumpah Palapa Sebagai Spirit Ibu Kota Nusantara - Robingun Suyud El Syam; Abdurrohman Al Asy’ari (Populer: Jurnal Penelitian Mahasiswa, 2023)
This article aims to reveal the heuristic value of the palapa oath as the spirit of the Nusantara Capital, by emphasizing the historical aspect of how the oath was motivated and applied along with its achievements. This study is a heuristic setting, qualitative analysis, studying sources systematically one by one descriptively. The conclusion of the study: that the heuristic value in the palapa oath is the idea of ​​knitting diversity within the framework of unity and equity in development and education which is used as the spirit of the Nusantara Capital City. This spirit is assumed to be able to overcome problems related to the issue of radicalization that threatens the disintegration of the nation, as well as issues of development and education equity which have so far hampered sustainable development and Indonesia's position at the international level. The research contributes as one of the reinforcements for government policies regarding the new capital city, and stimulates further, more specific research.